The association of FKBP5 polymorphisms with the severity of depressive disorder in patients with methamphetamine use disorders - Fang, Ting; Liu, Meng-Nan; Tian, Xiao-Yu; Lu, Guan-Yi; Li, Fei; Zhang, Xiaojie; Liu, Feng; Hao, Wei; Wu, Ning; Li, Hong; Li, Jin (Frontiers in Psychiatry, 2023)
Background: Cooccurring depressive disorder (DD) in patients of methamphetamine user disorder (MAUD) impacts the diagnosis, treatment, and prognosis of the disease. Although FKBP5 has been associated with a variety of psychiatric disorders, whether FKBP5 influences depression susceptibility in MAUD is unknown so far. Methods: Here, we sequenced six FKBP5 single nucleotide polymorphism (SNP) sites (rs4713916, rs6926133, rs9470080, rs737054, rs4713902, and rs9470079) in 282 methamphetamine users. The MAUD and DD were evaluated by the clinical questionnaires. SPSS was used to analyze the relationship between FKBP5 SNPs and DD in the MAUD individuals. Results: Of 282 methamphetamine users, 161 individuals met the MAUD criteria, and among them, 50 patients (31.1%) had DD cooccurring. Importantly, the incidence of DD in MAUD individuals was 3.314 times greater than that of the methamphetamine users who didn’t meet the MAUD criteria (p<0.001). Although none of the 6 SNPs of FKBP5 were correlated with the cooccurrence of DD in the MAUD population, two FKBP5 alleles (rs4713916A, rs6926133A) were substantially associated with the higher DD scores in the MAUD patients (p<0.05). Moreover, those with the two risk alleles have no much higher scores than that with a single risk allele, the strong linkage disequilibrium of the two SNPs may be the underlying cause of this result. Despite having weak linkage disequilibrium with either rs4713916 or rs6926133, FKBP5 rs9470079 became risky when paired with either. Conclusions: The results of this study revealed that the FKBP5 risk alleles (rs4713916A and rs6926133A) were associated with a greater probability of severe DD in MAUD patients. These findings here would help with the development of biological early warning markers and the creation of personalized treatment strategies for MAUD.